The Influence of Discipline and Learning Motivation on Student Learning Outcomes in Class VIII Social Studies Subjects at Darma Pertiwi Bahbutong Private Junior High School, Sidamanik T.A District 2022/2023 - Sari Helsyah Sitinjak; Benjamin Albert Simamora; Binsar Tison Gultom (Indonesian Journal of Advanced Research, 2023)
This study aims to determine how much influence discipline and learning motivation have on student learning outcomes in grade VIII at Darma Pertiwi Private Junior High School. This research is of Quantitative type. The sampling technique in this study is a purposive sample technique of 100 respondents. Collection techniques using Observation, Documentation, Questionnaires, Interviews. Instrument Test Using Classical Assumption Test and coefficient of determination test. Data from research and partial test data management (t-test) are known that tcount is obtained 3.863 > ttable 1.984 and significance 0.000 < 0.005 So it can be concluded that discipline has a significant effect on student learning outcomes in grade VIII at Darma Pertiwi Bahbutong Private Junior High School. From the partial test (t-test) it is known that a tcount of 2.960 > ttable 1.984 and a significance of 0.004 < 0.005 so that it can be concluded that according to learning motivation has a significant effect on learning outcomes in grade VIII at Darma Pertiwi Private Junior High School